Kainate receptors novel signaling insights - Rodriguez-Moreno, Antonio 1968-; Sihra, Talvinder S. 1960- (Advances in Experimental Medicine and Biology, 2011)
This volume critically examines the functional actions of the kainate--type glutamate receptors (KARs). Following on from the larger body of work on the NMDA-- and AMPA-type ionotropic glutamate receptors (GluRs), studies with KARs have consistently thrown up exceptions to general rules about synaptic modulation. Contributors herein provide an insight to the idiosyncracies that now almost typify the KAR field. The fascinating insights provided in this volume serve to encourage searching mechanistic questions.